Crisis of the Politics of the Presence: From Hannah Arendt to the Politics of the Difference - Urabayen, Julia; León, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
With the arrival of Modernity, philosophical reflection about politics had progressively penetrated into the relevance of public space as a place of appearance and, therefore, of action. These are the axes of Arendt’s work that seek to delimit the political space and the role of the citizenry at the moment of constituting and maintaining that space by way of action that requires presence. On the other hand, in Arendt’s thought one does not find an exploration of these new possibilities of action, or the absent political space, which are opened-up to us via the technologies of communication. In the following section the postures of Derrida and Virilio, authors that undertake a critique of the politics of presence, each investigating a different aspect, will be developed. Continuing along the line of Virilio’s critique, one arrives at the defense of the rhyzomatic multitudes that pursue “Open Source”, and which are defended by Negri as being a new political subject. This presupposes entering into the irremediable losses that the use of the CTI involve for a politics of presence.